19 + 5 = - 17p + 13p
24 = - 4p
p = - 6
2007-10-24 06:44:05
·
answer #1
·
answered by Como 7
·
1⤊
0⤋
Add 5 to both sides:
19 +5 -13p = -17p -5 +5
24 -13p = -17p
Add 13 p to both sides:
24 -13p +13p = -17p +13p
24 = -4p
Now divide both sides by -4:
24/(-4) = (-4/-4) *p
-6 = p
Check:
19-13(-6) = 19 + 78 = 97
-17(-6) -5 = 102 - 5 = 97
97=97, therefore, p = -6
2007-10-23 10:25:45
·
answer #2
·
answered by sayamiam 6
·
0⤊
0⤋
19 -13p = -17p-5 ADD 5 to both sides
19 - 13p + 5 = -17p - 5 + 5
24 - 13p = -17p ADD 13 p to both sides
24 - 13p +13p = -17p + 13p
24 = -4p DIVIDE both sides by -4
-24/4 = p
-6 = p ANSWER
CHECK in original equation
19-13p= -17p - 5
19-13(-6) = -17(-6) - 5
19 - (-78) = 102 - 5
97 = 97 The answer checks out
2007-10-23 10:30:38
·
answer #3
·
answered by Anonymous
·
0⤊
1⤋
Add 17p to both sides and subtract 19 from both sides
4p = -24
Divide by 4
p = -6
Check:
19 - 13(-6) = -17(-6) -5
19 + 78 = 102 - 5
97 = 97
2007-10-23 10:23:33
·
answer #4
·
answered by Ms. Exxclusive 5
·
0⤊
0⤋
19 - 13p = -17p - 5
-13p + 17p = -5 - 19
4p = -24
p = -6
Hope this helps!
2007-10-23 10:23:14
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
19-13p=-17p-5
19+5=-17p+13p
24=-4p
-6=p
2007-10-23 10:24:29
·
answer #6
·
answered by Ann 4
·
0⤊
0⤋
19-13p=-17p-5
-13p+17p=-5-19
4p=-24
p=-6
2007-10-23 10:24:24
·
answer #7
·
answered by freeky 2
·
0⤊
0⤋
17p - 13p = -19 - 5
4p = -24, p = -6
2007-10-23 10:29:18
·
answer #8
·
answered by tj is cool 5
·
0⤊
1⤋
Move the 'p's to one side, and the numbers to the other.
24=-4p
Divide -4 by both sides
p=-6
2007-10-23 10:24:42
·
answer #9
·
answered by Anonymous
·
0⤊
0⤋
Why don't you try to do one?
2007-10-23 10:23:17
·
answer #10
·
answered by oaksctp 2
·
0⤊
1⤋